Analisis Pelaksanaan Bantuan Pembiayaan Perumahan Berbasis Tabungan di Provinsi Sumatera Selatan - Fathan, Romel; Idi, Abdullah; Mardianto, Mardianto (@-Publik: Jurnal Administrasi Publik, 2022)
Article 28 of the 1945 Constitution states that "Everyone has the right to live in material and spiritual prosperity, to live, to have a good and healthy environment, and to have the right to health services. Meanwhile, the problem of buying a house is still a dilemma, especially for low-income people. This study aims to identify and analyze the application for Savings-Based Housing Financing assistance in South Sumatra Province. This research is a descriptive study using a qualitative approach. The data used is based on the type, which is quantitative data and qualitative data, while according to the source, it means primary data and secondary data. The data collection instruments used were observation, interviews and documentation. The informants in this study were the Head of the Department of Housing and Settlement Areas of South Sumatra Province; Secretary of the Department of Housing and Settlement Areas of South Sumatra Province; Head of Subdivision of Planning, Evaluation and Reporting of the Department of Housing and Settlement Areas of South Sumatra Province; Head of Housing Division of the Department of Housing and Settlement Areas of South Sumatra Province; Developer / Housing Developer in South Sumatra Province; Bank Implementing Savings-Based Housing Financing Program in South Sumatra Province; Community participants in the Savings-Based Housing Financing Assistance Program in South Sumatra Province. The data analysis in this research is a qualitative analysis with an interactive model. According to the results of the study, it can be concluded that the implementation of Savings-Based Housing Financing Assistance in South Sumatra Province has been carried out according to applicable procedures and regulations, although there are several obstacles faced by the implementation of the program.